PENGARUH RASIO KEUANGAN DAN FCF TERHADAP NILAI PERUSAHAAN: KEBIJAKAN DIVIDEN SEBAGAI PEMODERASI - Mayarina, Nana Ayu; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to test the influence of profitability, liquidity, leverage, and free cash flow to the firmvalue with dividend policy as the moderating variable. The population is all property and real estate companieswhich are listed in Indonesia Stock Exchange (IDX) during the 2011-2015 periods. The sample collection hasbeen carried out by using purposive sampling method. The data analysis technique has been done by usingmultiple linear regressions analysis and the interaction test is Moderated Regression Analysis (MRA) and theinstrument of IBM SPSS Statistics 20. The result of this research which has been done by using multiple linearregressions shows that profitability has positive influence to the firm value. Meanwhile the variables liquidity,leverage and free cash flow do not have any influence to the firm value. The result of the analysis research ofmoderating variable which has been done by using interaction test of Moderated Regression Analysis (MRA)shows that the dividend policy is only capable to moderate the influence of profitability to the firm value, but itdoes not capable to moderate the influence of liquidity, leverage, and free cash flow to the firm value.Keywords: Profitability, liquidity, leverage, free cash flow, firm value.